Synthesis and comparative biological analysis of mixed NHC/L platinum (II) complexes: anticancer and antimicrobial properties - Aslan, Sümeyye; Bugday, Nesrin; Boulebd, Houssem; Yüce, Hande; Türkmen, Neşe Başak; Özek, Dilan Aşkın; Ünüvar, Songül (Elsevier, 2026)
Platinum-N-heterocyclic carbene (Pt-NHC) complexes have garnered significant interest as potential anticancer agents, with their efficacy influenced by their structural characteristics and ligand environments. In this study, eight of Pt-NHC complexes were synthesized via a one-pot synthesis method from related NHC precursors, which have different electronic and steric properties, and fully characterized by (1H and 13C) NMR, HRMS, FT-IR spectroscopy, and elemental analysis. Their anticancer and antimicrobial properties were evaluated by investigating cytotoxicity, inhibition of cancer cell migration, antimicrobial and antifungal activities, and apoptotic effects. The Pt-NHC complexes demonstrated notable antiproliferative and anti-migratory effects against SHSY5Y (human neuroblastoma), A549 (human lung cancer), MDA-MB-231 (human breast cancer), and HeLa (human cervical cancer) cell lines, as well as significant antimicrobial activity against S. aureus, C. albicans, and MRSA strains. Molecular docking analyses were performed to explore interactions between the complexes and cancer cell targets. Variation in the Bax/Bcl-2 ratio highlighted differences in apoptotic regulation across cancer cell lines. Notably, the Pt-NHC complexes exhibited greater efficacy than cisplatin, underscoring their promise as candidates for drug development, although further investigation into the complex roles of Bax and Bcl-2 in apoptosis is needed for a comprehensive evaluation of these new therapeutic agents.
Keywords: Pt-NHC; Cisplatin; Apoptosis; Anticancer activity; Molecular docking